2015
DOI: 10.1021/acs.est.5b01227
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Chemiluminescence Generation during Advanced Oxidation of Persistent Halogenated Aromatic Carcinogens

Abstract: ABSTRACT:The ubiquitous distribution coupled with their carcinogenicity has raised public concerns on the potential risks to both human health and the ecosystem posed by the halogenated aromatic compounds (XAr). Recently, advanced oxidation processes (AOPs) have been increasingly favored as an "environmentally-green" technology for the remediation of such recalcitrant and highly toxic XAr. Here, we show that AOPs-mediated degradation of the priority pollutant pentachlorophenol and all other XAr produces an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(59 citation statements)
references
References 41 publications
6
52
0
1
Order By: Relevance
“…27, 36 We found that this is also the case in our study. The major quinoid intermediates produced by TCPs were identified by HPLC-UV method with the respective authentic compounds as standards.…”
Section: Resultssupporting
confidence: 88%
“…27, 36 We found that this is also the case in our study. The major quinoid intermediates produced by TCPs were identified by HPLC-UV method with the respective authentic compounds as standards.…”
Section: Resultssupporting
confidence: 88%
“…During our study of metal-independent hydroxyl/alkoxyl/ketoxy radical production by halogenated quinones and H 2 O 2 (or organic hydroperoxides) 20 21 22 23 24 25 , and their potential biological effects 26 , we found that unprecedented hydroxyl radical-dependent two-step chemiluminescence could be generated by polyhalogenated quinones and H 2 O 2 23 . Recently, we also observed an intrinsic CL generation by all 19 chlorophenols (the parent compounds of chlorinated quinones) and the classic • OH-generating Fenton system, even in the absence of fluorescent agents 27 . One notable general trend is that the CL intensity increases with increasing number of chlorine atoms on the phenolic ring.…”
mentioning
confidence: 84%
“…One notable general trend is that the CL intensity increases with increasing number of chlorine atoms on the phenolic ring. Interestingly and unexpectedly, the strongest CL emission was found to be produced by 2,3,5,6-TeCP, which is even stronger than the most-highly chlorinated PCP, and much more stronger than two other TeCP isomers (2,3,4,5-, and 2,3,4,6-TeCP) 27 . However, it remains unclear what is the underlying molecular mechanism.…”
mentioning
confidence: 93%
“…Among these aqueous organic contaminants, EDTA is one of the most potentially dangerous http pollutants since it is used in many products such as herbicides, fertilizers, detergents, decontaminants in the nuclear industry, etc [1][2][3][4]. EDTA is widely used for water decontamination purposes in nuclear industry for its unique spatial conformation which can bind strongly to most metals.…”
Section: Introductionmentioning
confidence: 99%